Translating linguistic time - Goldfajn, Tal (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
If Sartre is right and the tense of a text holds the key to its special strangeness (1947), how does this strangeness fare in translation? What can we learn from looking at the translation of grammatical tense and aspect in narrative texts in different languages? It is often simply assumed that translating grammatical cate gories of time in languages - because it has to do with what is considered the hard core of language, i.e. the grammar as opposed to the lexicon of the language - mainly involves mere linguistic constraints. Jakobson ’s famous motto (1987: 433) - “languages differ essentially in what they must convey and not in what they can convey”- would therefore suffice to tell the whole story about the way in which linguistic time is translated. This paper argues, however, that this is not the whole story: it argues that the choice of tense in translation is more than just a grammatical agenda, and may actually reflect a number of different commitments. Section 2 examines some intriguing tense changes in the translation of children ’s literature: it discusses the motivations behind these changes and shows that by changing the ‘how’ of the original story through the tense choice the entire subjective perspective of the text is altered. Section 3 identifies a few patterns in the translation of past distinctions in Modern Hebrew. It suggests that in contrast to the more diversified means of translating aspectual meanings in previous decades, a major trend in the last decade or so has been to reduce all past sphere distinctions essentially to one single form, i.e. the simple past tense. Finally section 4 deals with the classical problem regarding the Biblical Hebrew tenses and their translation; it shows that the translation of the biblical verbs may be strongly determined by the different linguistic ideas (and even systematic theories) the translators adopt regarding the Biblical Hebrew tenses. In all these cases then, we observe that the translation of temporal meanings involves not only a commitment to specific temporal interpretations but also a commitment to more subtle conceptions of subjectivity in translation, of literary conventions and linguistic ideas.